2020
DOI: 10.3390/ma13030719
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid TiO2-ZnO Nanomaterials Prepared Using Laser Ablation in Liquid

Abstract: Hybrids of semiconductor nanomaterials often demonstrate properties that are superior to those of their components. In this study, we prepared hybrid nanomaterials of TiO2 and ZnO, which are among the most actively studied semiconductors, by means of millisecond-pulsed laser and analyzed how their morphology, particle size, and surface composition depend on preparation conditions. A series of nanomaterials were obtained via sequentially ablating Zn and Ti metal plates (in different sequences) in water, while l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 51 publications
1
26
0
Order By: Relevance
“…The optimized oxygen-related defects by V O in the bandgap of TiO 2 could excite photo-generated electrons in TiO 2 by the illumination of visible light. [37][38][39] Therefore, it was found that the process of 10 s of TTIP purge time during TiO 2 deposition was appropriate for a visible-light phototransistor.…”
Section: Resultsmentioning
confidence: 99%
“…The optimized oxygen-related defects by V O in the bandgap of TiO 2 could excite photo-generated electrons in TiO 2 by the illumination of visible light. [37][38][39] Therefore, it was found that the process of 10 s of TTIP purge time during TiO 2 deposition was appropriate for a visible-light phototransistor.…”
Section: Resultsmentioning
confidence: 99%
“…The high energy from laser beam helps to dissociate the solid to generate vapour, plasma, or molten metal droplets. These intermediates will then react with liquid to produce specific compounds which will be developed as NPs [60] . For iron oxide NPs, they are synthesized by irradiating a metal (typically iron ore) submerged in a solvent (water, acetone, chloroform, ethanol, isopropanol, etc.)…”
Section: Synthesis Methods Of Mnps and Hybrid Mnpsmentioning
confidence: 99%
“…These intermediates will then react with liquid to produce specific compounds which will be developed as NPs. [60] For iron oxide NPs, they are synthesized by irradiating a metal (typically iron ore) submerged in a solvent (water, acetone, chloroform, ethanol, isopropanol, etc.) with a pulsed laser beam.…”
Section: Laser Ablationmentioning
confidence: 99%
“…Normally, titania is a white powder with the band gap energy of 3.0-3.2 eV, and it does not absorb light in the visible range [3] that limits its use in photocatalysis. To increase the effectiveness and widen the spectral range of its photocatalytic activity, doping [10][11][12], core@shell structures' formation [13], decoration [14], and the formation of complex composite/hybrid oxides [15,16] are considered.…”
Section: Introductionmentioning
confidence: 99%